Electrooptic and Dielectric Studies in Cadmium Sulphide Nanorods/Ferroelectric Liquid Crystal Mixtures. (10th October 2012) - Malik, Praveen; Chaudhary, Ashok; Mehra, Rohit; Raina, K. K.
Abstract : We present the results based on the electrooptic and dielectric studies in cadmium sulphide (CdS) nanorods/ferroelectric liquid crystal mixtures. Doping of CdS nanorods increases the spontaneous polarization and response time, which due to large dipole-dipole interaction and increase in anchoring energies exists between nanorods and FLC molecules. Dielectric measurements revealed a decrease ( ~ 40% for 0.3% CdS in FLC) in permittivity and dielectric strength in doped sample cell than pure FLC mixture. A decrease in dc conductivity and relaxation frequency with doping concentration was also noticed. The preexponent factor and fractional exponent factor are found as predicated by existing theories.